Pantomime as the original human-specific communicative system. Issue 2 (1st September 2020) - Zlatev, Jordan; Żywiczyński, Przemysław; Wacewicz, Sławomir
Abstract: We propose reframing one of the key questions in the field of language evolution as what was the original human-specific communicative system? With the help of cognitive semiotics, first we clarify the difference between signals, which characterize animal communication, and signs, which do not replace but complement signals in human communication. We claim that the evolution of bodily mimesis allowed for the use of signs, and the social-cognitive skills needed to support them to emerge in hominin evolution. Neither signs nor signals operate single-handedly, but as part of semiotic systems . Communicative systems can be either monosemiotic or polysemiotic —the former consisting of a single semiotic system and the latter, of several. Our proposal is that pantomime, as the original human-specific communicative system, should be characterized as polysemiotic: dominated by gesture but also including vocalization, facial expression, and possibly the rudiments of depiction. Given that pantomimic gestures must have been maximally similar to bodily actions, we characterize them as typically (1) dominated by iconicity, (2) of the primary kind, (3) involving the whole body, (4) performed from a first-person perspective, (5) concerning peripersonal space, and (6) using the Enacting mode of representation.